Temperature dependence of the (π, 0) anomaly in the excitation spectrum of the 2D quantum Heisenberg antiferromagnet. (18th June 2020) - Wan, W; Christensen, N B; Sandvik, A W; Tregenna-Piggott, P; Nilsen, G J; Mourigal, M; Perring, T G; Frost, C D; McMorrow, D F; Rønnow, H M
Abstract: It is well established that in the low-temperature limit, the two-dimensional quantum Heisenberg antiferromagnet on a square lattice (2DQHAFSL) exhibits an anomaly in its spectrum at short-wavelengths on the zone-boundary. In the vicinity of the point the pole in the one-magnon response exhibits a downward dispersion, is heavily damped and attenuated, giving way to an isotropic continuum of excitations extending to high energies. The origin of the anomaly and the presence of the continuum are of current theoretical interest, with suggestions focused around the idea that the latter evidences the existence of spinons in a two-dimensional system. Here we present the results of neutron inelastic scattering experiments and Quantum Monte Carlo calculations on the metallo-organic compound Cu(DCOO) D2 O (CFTD), an excellent physical realisation of the 2DQHAFSL, designed to investigate how the anomaly at evolves up to finite temperatures . Our data reveal that on warming the anomaly survives the loss of long-range, three-dimensional order, and that it is thus a robust feature of the two-dimensional system. With further increase of temperature the zone-boundary response gradually softens and broadens, washing out the anomaly. This is confirmed by a comparison of our data with the results of finite-temperature Quantum Monte Carlo simulations where the two are found to be in good accord. In the vicinity of the antiferromagnetic zone centre, there was no significant softening of the magnetic excitations over the range of temperatures investigated.